MODEL PENDUGA BERAT BAYI LAHIR BERDASARKAN PENGUKURAN LINGKAR PINGGANG IBU HAMIL - Chairunita Chairunita; Hardinsyah Hardinsyah; Cesilia Meti Dwiriani (Food and Nutrition Society of Indonesia, 2006)
Nutritional status of pregnant women can be measured by anthropometry which is simple and non expensive. Waist circumference of pregnant women (WCP) may reflects uterus and fetus growth. The objective of this study is to develop an estimation model of birth weight based on WCP during the third trimester. For this purpose 250 pregnant women were selected from six health centers and five midwife clinics of Tanah Sareal, Bogor. Body height and weight, waist and hip circumferences, mid-upper arm circumference, fundal height were measured on 28th, 32nd , and 36th week of gestation. Body weight prior to pregnancy, history of pregnancy and birth, and food consumption was collected through an interview. The results show the two most appropriate estimation models of birth weight are based on WCP (R2=28.58%) and body weight (R2=28.27%) on 28 week of gestation, with the equations are : birth weight = 166.4(WCP)3 - 977.6(WCP)2 + 1914.7(WCP) - 1246.6 and birth weight = 14.7(body weight)3 - 79.4(body weight)2 + 143.1(body weight) - 82.5. Further prospective study with larger sample size are required to develop an estimation model of birthweight.